2016
DOI: 10.1111/aogs.13008
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative evaluation in women with uterine leiomyosarcoma. A nationwide cohort study

Abstract: Preoperative diagnostic modalities appear to have low sensitivity for differentiating leiomyosarcoma from fibroids. In Norway, approximately 54% of uterine leiomyosarcoma are unidentified before surgery. MRI evaluation was the imaging modality with the greatest sensitivity in identifying leiomyosarcoma preoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
31
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 21 publications
2
31
0
3
Order By: Relevance
“…Consistently, three cases in our study have a diameter of mass less than 7 cm. In our study, the preoperative endometrial samplings of the cases had benign finding indicating the limited utility of endometrial sampling in detection of uterine leiomyosarcomas, as mentioned previous studies 14,15 .…”
Section: Discussionsupporting
confidence: 70%
“…Consistently, three cases in our study have a diameter of mass less than 7 cm. In our study, the preoperative endometrial samplings of the cases had benign finding indicating the limited utility of endometrial sampling in detection of uterine leiomyosarcomas, as mentioned previous studies 14,15 .…”
Section: Discussionsupporting
confidence: 70%
“…The FDA emphasizes [13] that sarcomas in women undergoing surgeries due to presumed myomas approaches 2-3% in those over 60 years [19][20][21]. It should be highlighted that leyomyosarcomas often are unidentified before surgery as showed the data from the Cancer Registry of Norway [22], and in the Norwegian cohort, power morcellation of LMS has not led to reduced survival. In our study the woman with LMS who underwent power morcellation is 1 of 3 women with the longest survival after LMS recognition from the case series.…”
Section: Discussionmentioning
confidence: 99%
“…There is no exposure to radiation and there is high contrast between structures in the female pelvis. Several studies have identified features of LMS on MRI utilizing intravenous contrast and diffusion‐weighted imaging (DWI), which can identify malignant lesions by a combination of intrinsic T 2 intermediate/hyperintensity, irregular margin, low apparent diffusion coefficient (ADC) value, hemorrhage, necrosis, avid enhancement, and/or rapid growth …”
mentioning
confidence: 99%
“…Several studies have identified features of LMS on MRI utilizing intravenous contrast and diffusion-weighted imaging (DWI), which can identify malignant lesions by a combination of intrinsic T 2 intermediate/hyperintensity, irregular margin, low apparent diffusion coefficient (ADC) value, hemorrhage, necrosis, avid enhancement, and/or rapid growth. [10][11][12][13][14][15][16][17][18][19][20][21][22] Based on these data, in late 2013 we created a preoperative protocol where we used MRI features to risk-stratify the appearance of fibroids in conjunction with our referring gynecologists, who used additional screening data such as total serum lactate dehydrogenase (LDH) 12 and endometrial biopsies to properly triage patients for appropriate fibroid treatment.…”
mentioning
confidence: 99%